1984
DOI: 10.1007/bf00541933
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adverse drug reactions in psychiatric hospitals

Abstract: A system for monitoring adverse drug reactions (ADR) in psychiatric inpatients was introduced in psychiatric hospitals in the FRG in May 1979. It consists of intensive drug monitoring (IDM) and a so-called "organized spontaneous reporting system" (OSR). ADR are rated separately according to impact on therapy and probability of causal relationship. With IDM all ADR (Grades I-III) are assessed in a randomly selected sample of inpatients. With OSR only ADR leading to discontinuation of the drugs in question (= AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…There was no difference in risk far male or female patients in tbis study, while other authors found a preponderance of men (I) or women (2). As to age groups, there was a tendency towards the more elderly patients in the ADR group which is consistent with other reports (1,2,4,5); nevertheless, as 45 % of our patients were under 50 years, age cannot be estimated as a very important factor. Although delirium due to psychotropic drugs seems to show symptoms that are not as severe as seen in delirium tremens (3), almost three quarters of our patients showed vegetative symptoms.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There was no difference in risk far male or female patients in tbis study, while other authors found a preponderance of men (I) or women (2). As to age groups, there was a tendency towards the more elderly patients in the ADR group which is consistent with other reports (1,2,4,5); nevertheless, as 45 % of our patients were under 50 years, age cannot be estimated as a very important factor. Although delirium due to psychotropic drugs seems to show symptoms that are not as severe as seen in delirium tremens (3), almost three quarters of our patients showed vegetative symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…Methods and first results of this study have been published earlier (4,9). From May 1979 to December 1983, alt inpatients of the Oepartment of Psychiatry in Munich treated with psychotropic drugs have been continually monitored by the methods of the Drug Monitoring system.…”
Section: Methodsmentioning
confidence: 97%
“…The probability rating is based on criteria described earlier [12]: ± Grade 1, possible: ADR not known, or time course or dosage unusual for imputed drug, or alternative explanation for ADR more probable. ± Grade 2, probable: ADR known with drug in question, time course and dosage in accordance with previous experience, alternative explanation less probable.…”
Section: Methodsmentioning
confidence: 99%
“…Relative frequencies that were based on "probable" and "definite" cases only, have been published by Grohmann et al (1). They are much lower.…”
mentioning
confidence: 92%
“…Dear Sir, This letter refers to the article entitled "Adverse drug reactions -an epidemiological study at psychiatric hospitals" by Schmidt et al (1).…”
Section: Letter To the Editormentioning
confidence: 99%